Individual differences in receptivity to scientific bullshit - Anthony Evans; Willem Sleegers; Žan Mlakar (Judgment and Decision Making, 2020)
Pseudo-profound bullshit receptivity is the tendency to perceive meaning in important-sounding, nonsense statements. To understand how bullshit receptivity differs across domains, we develop a scale to measure scientific bullshit receptivity — the tendency to perceive truthfulness in nonsensical scientific statements. Across three studies (total N = 1,948), scientific bullshit receptivity was positively correlated with pseudo-profound bullshit receptivity. Both types of bullshit receptivity were positively correlated with belief in science, conservative political beliefs, and faith in intuition. However, compared to pseudo-profound bullshit receptivity, scientific bullshit receptivity was more strongly correlated with belief in science, and less strongly correlated with conservative political beliefs and faith in intuition. Finally, scientific literacy moderated the relationship the two types of bullshit receptivity; the correlation between the two types of receptivity was weaker for individuals scoring high in scientific literacy.